Analisis Media Pembelajaran Yang Digunakan Guru Di SMKN Pertanian Terpadu Provinsi Riau - Nabila Yenanta; Desti; Nurkhairo Hidayati (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the use of instructional media by teachers in science learning at SMKN Pertanian Terpadu Provinsi Riau. The research employed a descriptive method with data collected through questionnaires and interviews. The questionnaire was administered to 20 eleventh-grade students to identify students’ perceptions of the instructional media used, while interviews were conducted with a science teacher to obtain more in-depth information regarding the implementation of instructional media in the classroom. The data were analyzed using descriptive quantitative and qualitative techniques. The results indicate that the instructional media used by teachers are generally appropriate to the learning material and easy for students to access; however, the media are considered less engaging and have not provided an optimal impact on students’ understanding. In addition, the interview results reveal that the use of instructional media has not been fully optimized due to several constraints. Therefore, the development of more engaging and student-oriented instructional media is needed to support more effective science learning.